2017
DOI: 10.1016/j.enbuild.2017.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Overview and future challenges of nearly zero energy buildings (nZEB) design in Southern Europe

Abstract: a b s t r a c tIn times of great transition of the European construction sector to energy efficient and nearly zero energy buildings (nZEB), a market observation containing qualitative and quantitative indications should help to fill out some of the current gaps concerning the EU 2020 carbon targets. Next to the economic challenges, there are equally important factors that hinder renovating the existing residential building stock and adding newly constructed high performance buildings. Under these circumstance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
143
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(150 citation statements)
references
References 40 publications
0
143
0
7
Order By: Relevance
“…Indoor air quality and energy saving of existing buildings are often considered as incompatible goals [1,2]. Nonetheless, the introduction of the new regulation on the performance of buildings [3], i.e., the introduction of nearly zero energy buildings (NZEBs) as the new building target [4,5], will force the building sector to handle simultaneously the heat losses and the air quality issues, since ventilation approaches not properly designed will likely not fulfill the limitation on energy need for space heating typical of the NZEBs [6][7][8]. Apart from new constructions, the strategic challenge in view of the reduction of the energy consumption of the building sector is the energy retrofit of the existing buildings [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Indoor air quality and energy saving of existing buildings are often considered as incompatible goals [1,2]. Nonetheless, the introduction of the new regulation on the performance of buildings [3], i.e., the introduction of nearly zero energy buildings (NZEBs) as the new building target [4,5], will force the building sector to handle simultaneously the heat losses and the air quality issues, since ventilation approaches not properly designed will likely not fulfill the limitation on energy need for space heating typical of the NZEBs [6][7][8]. Apart from new constructions, the strategic challenge in view of the reduction of the energy consumption of the building sector is the energy retrofit of the existing buildings [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…A few years later, a revised text was approved, Directive 2010/31/EU, known as the EPDB Recast [2]. Thus, the regulations on Nearly Zero Energy Buildings, known as NZEBs, were introduced for all new buildings from year 2020 onwards [3]. This text was revised in 2012 and has now become Directive 2012/27/EU [4].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve these goals of very low or nearly zero energy consumption in the building section, an innovative concept of nearly zero energy buildings (nZEBs) representing high-performance buildings was proposed [9,10]. The nZEB refers to the low energy consumption of buildings by adopting energy-saving technologies or renewable energy measures [11,12]. A great number of studies have been conducted on energy-saving technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the building with only high-efficiency PV modules comes closest to reaching a zero energy balance. Wu et al [37] found that ground source heat pump (GSHP) used less energy than the air source heat pump (ASHP) Energies 2019, 12,4734 3 of 31 in 11 out of 15 zones across the United States, particularly in cold climate zones like Chicago through Duluth, where savings ranged from 24.3% to 39.2%.…”
Section: Introductionmentioning
confidence: 99%